ANALISIS KELAYAKAN MENGGUNAKAN HAMDI’S METHOD PADA USAHA AGROINDUSTRI TAPAI UBI KAYU PAK ZAIN DI KECAMATAN RUMBAI BARAT KOTA PEKANBARU - Setiawan, Rahmat; Hamdi Agustin; Doni Giong Saputra (JSE: Jurnal Sharia Economica, 2026)
This study aims to analyze the feasibility of Pak Zain's cassava tapai agro-industry business using Hamdi's Method consisting of the Gold Value Method (GVM) and the Gold Index (GI). The research method used is a quantitative approach with a case study on Pak Zain's cassava tapai agro-industry business in Pekanbaru. The results of the study show that Pak Zain's cassava tapai agro-industry business using Hamdi's Method consisting of the Gold Value Method (GVM) obtained a positive gold value of 115.094 grams, which indicates that the investment for the business is feasible. The Gold Index (GI) value = 3.822 grams because GI> 1, then the cassava tapai business is declared feasible to run based on the GI criteria. As a comparison, using a conventional perspective, namely NPV and PI, produces NPV = Rp. 409,328,230.16 (positive) / (NPV > 0), so that the business is financially feasible to run according to the NPV decision criteria (NPV > 0 = feasible). Then, the Profitability Index value is 12.87 (PI) > 1, so that Mr. Zain's cassava tapai agro-industry business is profitable and feasible. From the results of the business feasibility analysis, it can be identified that Mr. Zain's cassava tapai agro-industry business in Pekanbaru city is financially feasible. The Hamdi's Method is effectively used for business feasibility analysis.